Strategi Pengembangan Bahan Ajar Bahasa Arab Berbasis Kurikulum Merdeka: Inovasi, Implementasi, dan Evaluasi - Azzah Fadiyah Nurfadhilah Fahman; Andi Abdul Hamzah (Lembaga Pengembangan Kinerja Dosen, 2025)
This research uses a library research method which analyzes how the syllabus and learning plan are designed as well as what materials are used and what approach methods are used. The aim of this research is to find out what syllabus designs, learning plans and materials and approach methods are used in the curriculum. understanding the curriculum as a systematic learning guide, preparing syllabi, and implementing innovative and contextual learning approaches. The process of developing teaching materials is carried out through the stages of analysis, design, development, evaluation and revision. It is hoped that the development of curriculum-based teaching materials will be able to create an Arabic language learning process that is more meaningful, enjoyable and in line with the demands of the digital era. So the author presents the conclusions from various sources in this article.